Efficacy of a combined diving and mindfulness program on emotional eating in adults with obesity: Randomised controlled trial with standard care - Karolina Griffiths; Thibaut Markarian; Vincent Meurice; Mélanie Muzellec; Fanny Lannoy; Frederic Beneton; Pierre Michelet (PLoS ONE, 2026)
Background Emotional eating is considered as a mediator between depression and obesity. Combining mindfulness and sport activities can improve obesity-related psychological disorders but inconsistencies in effect and duration have been reported. We aimed to evaluate the effects of a combined mindfulness-diving Bathysmed® program on emotional eating scores in participants with obesity. Methods This unblinded randomized controlled trial was performed in the community setting, Montpellier, France. Adults with a BMI > 30 kg/m2 were randomly assigned (1:1) to a Bathysmed® 2-month program (intervention group) therapeutic scuba-diving protocol with mindfulness exercises plus standard care, or stand-alone standard care including dietary and psychological support (control group). The primary outcome was the mean change in the emotional eating subscale of the Dutch Eating Behaviour Questionnaire (DEBQ-EE) at 2-months as intention to treat. Findings Between July-August 2022, 63 participants were randomised, with 31 in the intervention group. One participant from each group were excluded. Fifty-five (87·3%) were female, median age 46 [35.5;54] and BMI 35.46 [33.45;39.48]. There was a statistically significant reduction of DEBQ-EE at 2 months in the intervention group (−0·82 (SD 0·81)) versus control group (−0·27 (SD 0·61) p = 0·004). This effect was maintained at 5 and 8-month follow up. There was a significant reduction in weight self-stigma, stress, and quality of life change scores in the intervention group. Interpretation This combined diving and mindfulness program effectively reduces emotional eating, self-stigma and quality of life scores in participants with obesity, with sustained benefits. Health policies should integrate physical activity and psychological therapies for obesity management. Trial registration Clinicaltrials NCT06882200 .